2010
DOI: 10.1016/j.hrtlng.2009.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prevalence of symptoms of depression, anxiety, and hostility in elderly patients with heart failure, myocardial infarction, and a coronary artery bypass graft

Abstract: 2016-03-19T19:12:06

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
1
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 49 publications
6
88
1
8
Order By: Relevance
“…[841][842][843] Although it might be assumed that depression occurs only among hospitalized patients, 844 a multicenter study demonstrated that even at least 3 months after a hospitalization, 63% of patients with HF reported symptoms of depression. 845 Potential pathophysiologic mechanisms proposed to explain the high prevalence of depression in HF include autonomic nervous system dysfunction, inflammation, cardiac arrhythmias, and altered platelet function, but the mechanism remains unclear. 846 Although remission from depression may improve cardiovascular outcomes, the most effective intervention strategy is not yet known.…”
Section: Depressionmentioning
confidence: 99%
“…[841][842][843] Although it might be assumed that depression occurs only among hospitalized patients, 844 a multicenter study demonstrated that even at least 3 months after a hospitalization, 63% of patients with HF reported symptoms of depression. 845 Potential pathophysiologic mechanisms proposed to explain the high prevalence of depression in HF include autonomic nervous system dysfunction, inflammation, cardiac arrhythmias, and altered platelet function, but the mechanism remains unclear. 846 Although remission from depression may improve cardiovascular outcomes, the most effective intervention strategy is not yet known.…”
Section: Depressionmentioning
confidence: 99%
“…Psychological distress 123 and decreased sexual function or activity 2,3 are associated 124 and are common in patients with CVD. In patients with CAD, 2,3 heart failure, 51 CHD, 67 recent MI, 125 CABG, 126 ICD implantation, 64 or cardiac transplantation, 127 sexual activity frequency and satisfaction often decline because of anxiety on the part of the patient or partner that sexual activity will worsen the underlying cardiac condition or cause death.…”
Section: Levine Et Al Sexual Activity and Cardiovascular Diseasementioning
confidence: 99%
“…There are established links between depression and heart disease (Kent and Shapiro 2009) and a substantial body of research has highlighted the psychological problems of many patients with HF. The prevalence of depression and anxiety is high in chronic heart failure (10-60% depression; 11-45% anxiety); with rates of depressive disorders 2 to 4 times higher in chronic heart failure patients than in the general population (Ladwig et al 2014) and higher in heart failure patients than other cardiac patient groups (Moser et al 2010).…”
Section: Introductionmentioning
confidence: 99%